Fargo. Year two [videorecording (DVD)]. - Dunst, Kirsten, 1982-; Plemons, Jesse, 1988-; Danson, Ted, 1947-; Wilson, Patrick, 1973- (20th Century Fox Home Entertainment, 2016)
The second chapter is set in 1979 in Sioux Falls, South Dakota, and Luverne, Minnesota, where young State Police Officer Lou Solverson, recently back from Vietnam, will tackle an all-new 'true crime' case.